Perancangan Alat Pemberi Pakan Dan Monitoring Sisa Pakan Kucing Berbasis Internet Of Things (IOT) - zuhri, khozainuz; Sari, Resy Anggun; Putra, Fajri Aditya (Jurnal Teknologi dan Informatika (JEDA), 2024)
The advances in technology that occur today have resulted in many people's need for technology also increasing. For example, the use of internet of things (IoT) technology in cat feeding equipment. When keeping cats, there are still many people who feed their cats directly or manually. And feeding is sometimes irregular. This disrupts the activities of cat owners because they always have to feed them manually. And sometimes cat owners have to leave their cats in animal care because they are not at home for a long time. This research uses the Research and Development (RD) system development method, a research methodology that aims to build and validate tools. Tools produced using Research and Development (RD) techniques will be more effective. As well as the system design method using UML (Unified Modeling Language). The IoT cat feeding tool and IoT cat GPS have succeeded in solving all existing problems, all the functions of the tools run well and are in accordance with their respective uses. The NodeMCU ESP8266 can manage all components in the research and the neo6m GPS is used to detect the presence of cats, and the monitoring camera can be informed into the blynk application.